Boosting Early Reading Skills with Alphabet Puzzle Media: The Effectiveness of Positive Reinforcement - Maghfiroh Mutiarasari; Nadhirotul Laily (Psikostudia : Jurnal Psikologi, 2024)
One of the learning media that can be used to support the development of children's reading skills is letter puzzles. This media is chosen because it can capture children's attention through its varied shapes and colors. The goal is to evaluate the effectiveness of the intervention using letter puzzle media in improving pre-reading skills in preschool-aged children. This study is designed with an experimental approach to assess the effectiveness of the intervention using letter puzzle media in enhancing pre-reading skills in preschool-aged children. The research results show that the implementation of positive reinforcement is proven effective in improving reading skills in early childhood, including through increased learning motivation, self-confidence, and self-regulation. The implications of these findings suggest that providing positive reinforcement not only accelerates the learning process but also builds a foundation of positive character that can support children's future academic and social success.Salah satu media pembelajaran yang dapat digunakan untuk mendukung perkembangan keterampilan membaca anak sebagai puzzle huruf. Media ini dipilih karena mampu menarik perhatian anak-anak melalui bentuk dan warna yang bervariasi. Tujuan untuk mengevaluasi efektivitas intervensi menggunakan media puzzle huruf dalam meningkatkan keterampilan pra-membaca pada anak-anak usia prasekolah. Penelitian ini dirancang dengan pendekatan eksperimen untuk mengevaluasi efektivitas intervensi menggunakan media puzzle huruf dalam meningkatkan keterampilan pra-membaca pada anak-anak usia prasekolah. Hasil penelitian bahwa penerapan reinforcement positif terbukti efektif dalam meningkatkan kemampuan membaca pada anak usia dini, baik melalui peningkatan motivasi belajar, rasa percaya diri, maupun kemampuan pengendalian diri. Implikasi dari temuan ini menunjukkan bahwa pemberian reinforcement positif tidak hanya mempercepat proses pembelajaran, tetapi juga membangun fondasi karakter positif yang dapat mendukung keberhasilan akademik dan sosial anak di masa mendatang.